"SWING": A European project for a new application of an ionospheric network. Issue 5 (11th May 2016) - Zolesi, B.; Bianchi, C.; Meloni, A.; Baskaradas, J. A.; Belehaki, A.; Altadill, D.; Dalle Mese, E.
Abstract: The SWING (Short Wave critical Infrastructure Network based on a new Generation high survival radio communication system) is a European project aimed at studying a high survival high‐frequency (HF) radio network to link European Critical Infrastructures (ECIs). This system is thought to replace broadband internet communication, maintaining the minimum flux of essential information for the ECIs management and control, in case of wide‐scale threats, including terrorist attacks, able to put out of order internet links over the Mediterranean region. SWING is designed to evaluate the threat and increase the security awareness, as well as the level of protection, of analogous and/or interdependent ECIs. In order to meet these goals, SWING was finalized to recognize how and when the internet communication fails and to develop the standard software and hardware tools necessary for implementing communication protocols suited for a reliable and interoperable short‐wave (SW) or high‐frequency (HF) radio network backup. The internet broadband description and internet failure recognition were taken into consideration in the project but are not treated in this paper. It has been assessed that in case of complete failure of the internet broadband communication fundamental information for the management and control of ECIs over the Mediterranean region can be maintained with a HF network, even in case of moderate ionospheric perturbations. Key Points: EU project aimed at studying a high survival HF radio network to link Critical Infrastructures Short‐wave or high‐frequency (HF) radio network backup Radio communication maintained even in case of moderate ionospheric perturbations